Identification of salmonella strains isolated from mussel, oyster, and their culture environment through culture dependent method and phylogenetic analysis - Galon, Byrille Tiara M.
Concerns regarding pathogenic bacterial and viral contamination on bivalves have raised awareness on the risks associated with raw and partially-cooked consumption of seafood. Salmonella poisoning is identified as a globally alarming issue implicating shellfishes. The great diversity and variations within Salmonella renders this genus as one of the complicatedly isolated organism. With about 2,443 prevailing serovars to date, the presence of closely related cross-reactive bacteria could result to false-positive identification. Hence, the use of conventional biochemical methods often leads to erroneous interpretations. In the present study, presumptive Salmonella strains were isolated from fresh mussel, oyster and seawater. Isolates were characterized by phenotypic enrichment and biochemical tests and were shown to be putative Salmonella strains. To confirm the identity of the strains, phylogenetic analysis through the sequencing of the PCR-amplified 16S rRNA gene was conducted. Results showed that all the isolates are not related to any Salmonella species. The presumptive Salmonella strains are instead phylogenetically related to Proteus, Shewanella and Bacillus species. These findings points to the fact that false-identification of Salmonella using conventional culture-dependent technique is possible and that molecular-based methods may be a better alternative for rapid, highly specific and objective identification of Salmonella serovars. Further, the discovery of other bacterial pathogens other than Salmonella constitutes another hazard for the risk of foodborne diseases.